KloningOpen Reading Frame (orf) ESAT-6 (Early Secretory Antigenic Target-6) Mycobacterium tuberculosis ke Escherichia coliBL21 (DE3) - Agus, Rosana; Maidin, Asaad; Hatta, Mochammad; S.Retnoningrum, Debbie (Jurnal Kedokteran YARSI, 2008)
Tuberculosis (TB) caused by Mycobacterium tuberculosis is an infectious diseases leading to significant death toll in most partof the world. Vaccination with BCG, a TB vaccine, is still a common practice until now. In general, the people in Indonesia receive BCG vaccine during their early childhood, but the efficacy of the vaccine would not last long to adulthood, which allow themto get potential latent TB infection. This latent TB infection might be detected by tuberculin skin test (TST), however, the weakness is that false positive reactions are commonly found due to cross reaction between antibodies produced during BCG vaccination and purified protein derivative (PPD). Alternatively, its detection could be performed by identifying immunodominant antigen to M. tuberculosis. The Early Secretory AntigenicTarget-6 (ESAT-6) for antibody based serological detection with high sensitivity and specificity could also be applied. The purpose of this study was to clone the open reading frame (orf) of ESAT-6 from Mycobacterium tuberculosis into Escherichia coli BL21 (DE3). In this method, orf ESAT-6 was ligated to the expression vector pET-32b and transformed into E. coli BL21 (DE3). Characterization of clones was carried out by cutting the recombinant plasmid using restriction enzymes BamH1 and XhoI. The result showed that three colonies with recombinant plasmid pET-32b-ESAT-6 were obtained. Sequencing of the DNA insert was then performed using the universal T7 primer. Characterization of white colonies with restriction enzymes showed two bands i.e. 288 bp and 5900 bp for orf ESAT-6 and pET32b vector respectively. BLAST analysis of sequence showed 100% homology.